INTERCULTURAL COMMUNICATION - Turg’unova Shaxlo; G’aniyeva Tohira (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
The author conducts globalization impact conceptual analysis on the national culture and cultural identity formation and development in contemporary societies. The main focus is driven on such issues, as the globalization phenomenon, the extent to which national cultures are exerted influence by globalization, as well as threats and opportunities produced by globalization that reflect on cultures.